THE EFFECT OF GIVING CUCUMBER JUICE ON HIGH BLOOD PRESSURE IN PREGNANT WOMEN IN THE WORKING AREA OF PONDOK TINGGI PUBLIC HEALT CENTER, SUNGAI PENUH CITY IN 2022 - Sesmi Nanda Oktavia; Armita Sri Azhari; Eza Meydia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Based on the background, the problem in this study is